2015
DOI: 10.3233/aic-140618
|View full text |Cite
|
Sign up to set email alerts
|

Graph constrained label propagation on water supply networks

Abstract: In many real-world applications we have at our disposal a limited number of inputs in a theoretical database with full information, and another part of experimental data with incomplete knowledge for some of their features. These are cases that can be addressed by a label propagation process. It is a widely studied approach that may acquire complexity if new constraints in the new unlabeled data that should be taken into account are found. This is the case of the membership to a group or community in graphs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Sometimes, prior expert knowledge can be introduced in the form of rules (Gibert et al, 2010b) or ontologies (Gibert et al, 2014) to introduce semantic information into the process, and get classes easier to interpret. Graph theory (Herrera et al, 2015;di Nardo et al, 2018) and social network theory (Campbell et al, 2016;Brentan et al, 2017aBrentan et al, , 2018a have also found applications in clustering. Density-based methods, like DBScan (Ester et al, 1996) or OPTICS (Ankerst et al, 1999) are computation-based methods detecting areas with higher concentration of objects and work well with non-globular clusters.…”
Section: Profiling Dm Methods: Clustering and Density Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, prior expert knowledge can be introduced in the form of rules (Gibert et al, 2010b) or ontologies (Gibert et al, 2014) to introduce semantic information into the process, and get classes easier to interpret. Graph theory (Herrera et al, 2015;di Nardo et al, 2018) and social network theory (Campbell et al, 2016;Brentan et al, 2017aBrentan et al, , 2018a have also found applications in clustering. Density-based methods, like DBScan (Ester et al, 1996) or OPTICS (Ankerst et al, 1999) are computation-based methods detecting areas with higher concentration of objects and work well with non-globular clusters.…”
Section: Profiling Dm Methods: Clustering and Density Estimationmentioning
confidence: 99%
“…A hybrid combination SOM+k-Means Clustering was used to improve planning, operation and management of Water Distribution Systems in Brentan et al (2018b), which can be easily extended to other environmental problems, etc. Graph theory (Herrera et al, 2015;di Nardo et al, 2018) and social network theory (Campbell et al, 2016;Brentan et al, 2017aBrentan et al, ,2018a have been used to cluster a water distribution network into sectors so as to optimize these infrastructures' management. In Blanco et al (2018) SCADA data is used to identify health profiles of wind turbines.…”
Section: Applications and Referencesmentioning
confidence: 99%